PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS KEHUTANAN KABUPATEN MAMUJU UTARA - Ilyas, Sriyanti (Katalogis, 2018)
This study aimed to determine how much the influence of competence partially and simultaneously on employee performance at North Mamuju Department of Forestry. The competence theory used was of Spencer and Spencer comprising five competence characteristics, namely motive, trait, self-concept, knowledge, and skill, while the performance theory used was of Hasibuan consisting of ability, effort, and opportunity. The type of this research was quantitative and descriptive. The population of this study was the staff of North Mamuju Department of Forestry composed of 60 respondents. The sampling technique used was census, so that the entire population was sampled. The data analysis technique used was multiple linear regression. The results showed that: (1) the influence of competence simultaneously on employee performance at North Mamuju Department of Forestry had been being determined by motive, trait, self-concept, knowledge, and skill at 68.2% and in a very strong relationship. The dimension whose a high value of regression coefficient was motive, while the one whose a low was skill, especially the indicator of ability to organize work, meaning that the employees were less skilled in organizing their works; (2) the influence of competence partially on employee performance at North Mamuju Department of Forestry had been being determined by the influence of motive on employee performance, the influence of trait on employee performance, the influence of self-concept on employee performance, the influence of knowledge on employee performance, and the influence of skills on employee performance.